Utilization of Fibonacci Algorithm to Determine Product Bundling Discounts in Culinary Business - Aziman, M. Fauzan; Sutabri, Tata (International Journal Scientific and Professional, 2025)
Micro, small, and medium-scale culinary businesses (MSMEs) often face challenges in determining product bundling discount strategies due to limitations in data analysis. This study examines the effectiveness of implementing the Fibonacci algorithm in determining food product bundling discounts to increase sales and profitability. The method used is a quantitative experiment with an algorithm simulation approach, where discounts are determined based on the Fibonacci number sequence (1%, 2%, 3%, 5%, 8%, etc.). Data were obtained from the Lumpia Beef Lumer culinary MSME in Bekasi Regency and analyzed using Python, while the results were visualized in a soft Excel document. A comparison graph of the number of sales and income before and after the application of discounts was compiled in Excel based on daily transaction data. The results show an increase in sales volume of 60% and gross income of 60% after this strategy was implemented. The tiered discount strategy based on Fibonacci has proven attractive to customers, encouraging bundling purchases without significantly reducing profit margins. This approach offers a systematic and adaptive data-driven solution and can be used by other MSMEs to develop more effective and sustainable marketing strategies.